Utilization of Multimedia in Moral Aqidah Learning to Increase Learning Motivation at MTs Al-Atiqiyah - Nuranisa Nuranisa; Ulfatussadiyah Ulfatussadiyah; Siti Fadilah; M.Agung Sumarna; Adi Rosadi (Penerbit Presisi Pustaka, 2025)
This study aims to analyze the use of multimedia in learning Akidah Akhlak to improve students' learning motivation at MTs Al-Atiqiyah. The main problem raised is the low motivation of students to learn which has an impact on the lack of participation in the learning process. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation of teachers, students, and principals. The results of the study indicate that the use of multimedia such as videos of prophet stories, prayer movement animations, and interactive presentations has been proven to be able to increase students' focus, enthusiasm, and participation in learning. Teachers feel helped in delivering material in a more contextual and interesting way, while students state that they find it easier to understand the material and find learning more enjoyable. School support for the provision of multimedia facilities is an important factor, although there are still obstacles such as limited devices and technical skills of teachers. The conclusion of this study is that the use of multimedia in a planned and contextual manner can be an effective strategy in improving students' learning motivation in Islamic Religious Education subjects. The implication is that strengthening facilities and teacher training needs to be continuously improved to support learning innovation in the madrasah environment.